Hello from MrBillDoesMath!
Answer:
See Discussion below
Discussion:
A function f is even if f(-x) = f(x)
f(x) f(-x) Are they equal?
----------------------------------------------------------------------------------------
-x^8 + 2x^6-5x -(-x)^8 + 2(-x)^6 + 5x No
3 abs(x) - 4 3 abs(-x) -4 Yes
log5 x^2 log5 (-x)^2 Yes
(6x)^ (1/7) (-6x)^(1/7) No
e^(x^2-x) e^( (-x)^2+x) No
(x^8 +5x^2)^(-1) ( (-x)^8 + 5 (-x)^2) ^(-1) Yes
Answers with Yes, above are even functions.
Regards,
MrB
P.S. I'll be on vacation from Friday, Dec 22 to Jan 2, 2019. Have a Great New Year!
Answer:
what a confusing question?
Step-by-step explanation:
im guessing 3 feet
Answer:
3(x-2)+x=4x+6
Step-by-step explanation:
case 1) we have
3(x-2)+x=4x-6
Solve for x
3x-6+x=4x-6
4x-6=4x-6
0=0 ----> is true for any value of x
therefore
The equation has infinite solutions
case 2) we have
3(x-2)+x=2x-6
3x-6+x=2x-6
4x-2x=-6+6
2x=0
x=0
case 3) we have
3(x-2)+x=3x-3
3x-6+x=3x-3
4x-3x=-3+6
x=3
case 4) we have
3(x-2)+x=4x+6
3x-6+x=4x+6
4x-4x=6+6
0=12 ------> is not true
therefore
The equation has no solution
Answer:
Step-by-step explanation:
Profit, P(x), is the difference between revenue, R(x), and cost, C(x)
R(x) = 2x^4 - 3x^3 + 2x - 1
C(x) = x^4 -x^2 + 2x + 3
Substituting into the equation
P(x) = R(x) - C(x)
= (2x^4 - 3x^3 + 2x - 1) - (x^4 -x^2 + 2x + 3)
= x^4 - 3x^3 + x^2 - 4
The answer is the lower left option.
You need to divide 2 by four which equals 8, you need 8 pounds